THE CULTURE OF COMMUNITY DRAWING AS A SOURCE OF IDEAS IN DIGITAL ILLUSTRATION WORKS - Ali Mukhlas; Bangkit Sanjaya (Eduarts: Jurnal Pendidikan Seni, 2025)
The Rerajahan culture in traditional Islamic society is part of a spiritual practice that contains visual symbols with powerful religious, medicinal, and cultural meanings. The creation of this work aims to explore and re-visualize the symbolic richness of the Rajah tradition as a source of ideas for digital illustration works that are able to re-represent these spiritual and cultural values in the context of contemporary art. The methods used include literature studies on Islamic medical books, interviews with Rajah practitioners, and creative exploration through stylistic and symbolic approaches in the creation process. Bitmap-based digital drawing techniques with an emphasis on lines, pointillist, and black and white are used to strengthen the spiritual and emotional nuances of the visualized symbols. The results of the creation are three two-dimensional digital illustration works. This work demonstrates that digital illustration is not only effective as a medium for visual expression, but also as a space for spiritual education and cultural preservation. The creation of this work contributes to reviving traditional symbols into the realm of modern art that is more open, contextual, and relevant for today's generation, while bridging religious teachings and contemporary visual narratives.